Hydrogen‐Associated Filling‐Controlled Mottronics Within Thermodynamically Metastable Vanadium Dioxide - Xuanchi Zhou; Yongjie Jiao; Wentian Lu; Jinjian Guo; Xiaohui Yao; Jiahui Ji; Guowei Zhou; Huihui Ji; Zhe Yuan; Xiaohong Xu (Advanced Science)
Abstract The discovery of hydrogen‐associated topotactic phase modulations in correlated oxide system has emerged as a promising paradigm to explore exotic electronic states and physical functionality. Here hydrogen‐induced Mott phase transitions are demonstrated for metastable VO2 (B) toward new electron‐itinerant hydrogenated phases via introducing non‐equilibrium condition, delicately delivering a rich spectrum of hydrogen‐associated electronic states. Of particular interest, the highly robust but reversible hydrogenated phase achievable in metastable VO2 (B) significantly benefits protonic device applications, which is in contrast with well‐known VO2 (M1), where the metallic hydrogenated phase readily turns into insulating state with extensive hydrogen doping. Establishing correlated VO2 at metastable status fundamentally surpasses the thermodynamic restrictions to expand the adjustability in their electronic structure, giving rise to new electronic states and a superior resistive switching of 102–105 to the counterparts in widely‐reported VO2 (M1). Utilizing the theoretical calculations and synchrotron radiation analysis, the hydrogen‐associated phase modulation in metastable VO2 (B) is dominantly driven by band‐filling‐controlled orbital reconfiguration, while the concurrent structural evolution unveils a strong ion‐electron‐lattice coupling. The present work provides fundamentally new tuning knob for adjusting the energy landscape of electron‐correlated system, advancing the rational design of unachievable electronic states in hydrogen‐related equilibrium phase diagram.